Wybór i nieokreśloność jako komponenty semantyczne przymiotnika dowolny - Maciej Grochowski (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2017)
The article discusses syntactic and semantic features of the adjective dowolny ‘any’. The adjective in question refers to an object that the speaker intends to choose from a set of many elements. However, it doesn’t matter which object will be chosen. In the moment of choice the object loses its feature of “anyness”. The nominal phrase with the adjective dowolny represents indefinite description and this phrase can occur only in non-declarative sentences. The adjective dowolny is semantically related to the pronouns with the morpheme -kolwiek ‘any’.